A Two-Species Cooperative Lotka-Volterra System of Degenerate Parabolic Equations - Jiebao Sun; Dazhi Zhang; Boying Wu (Abstract and Applied Analysis)
We consider a cooperating two-species Lotka-Volterra model of degenerate parabolic equations. We are interested in the coexistence of the species in a bounded domain. We establish the existence of global generalized solutions of the initial boundary value problem by means of parabolic regularization and also consider the existence of the nontrivial time-periodic solution for this system.